Sagot :
Sulution;[tex] \\ [/tex]
[tex]A.) \: \blue{\tt{ 2x + 3 = x + 15}}[/tex]
[tex]\tt{2x + 3 = x + 15} \\\tt{2x+3−x=x+15−x} \\ \tt{x+3=15} \\ \tt{x+3−3=15−3} \\\green{\bold{x=12}}[/tex]
Answer;
[tex]\green{\bold{x = 12}}[/tex]
Sulution;
B.) (x + 1) / (x + 2) = 3/4
(x + 1) / (x + 2) = 3/4
4x + 4 = 3x + 6
4x + 4 - 3x = 3x + 6 - 3x
x + 4 = 6
x + 4 - 4 = 6 - 4
x = 2
Answer;
[tex]\green{\bold{x = 2}}[/tex]
[tex] \\ \\ [/tex]
[tex] \huge\tt\color{pink}{@Pentol} [/tex]
Answer:
2x+3=x+15
2x-x=15-3
x=12
(x+1)/(x+2)=3/4
(x+1)4=3(x+2)
4x+4=3x+6
4x-3x=6-4
x=2
Step-by-step explanation: